Academic Advising as a Predictor of Graduates’ Quality in Educational Management Programmes at Universities in North Eastern Nigeria - Bambi, Babatunde Ishola; Gayus, Diana Beatrice; Angyu, Lahiru Daniel (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2024)
This study investigated academic advising as a predictor of graduates' academic quality in Educational Management Undergraduate Programme in Universities in North Eastern, Nigeria. The study adopted a predictive survey research design. One hypothesis, together with two research questions, were developed and assessed at the 0.05 level of significance. The target population of the study is 766 respondents in public universities offering Educational Management (EDM) Undergraduate Programme in North Eastern, Nigeria. The sample of the study was 383 respondents (i.e., 28 staff and 355 students) which was selected using a multistage sampling technique. Two instruments titled: “Academic Advising Questionnaire (AAQ)” and a proforma on Educational Management Graduates’ CGPA were used for data collection. The instruments were validated and pilot-tested with Cronbach's Alpha statistic showing a reliability co-efficient of 0.85. The obtained data were examined using mean and standard deviation; while simple linear regression analysis was then employed to test the hypothesis at the 0.05 level of significance. The findings showed that: academic advising (F (1, 150) = 125.23, p < 0.05) predicts graduates' academic quality in Educational Management programs in Universities in North Eastern, Nigeria. Hence, the study concludes that academic advising significantly predicts graduates' academic quality within the Educational Management Undergraduate Programme in Universities in North Eastern Nigeria. The study recommended among others that university management should invest in training and professional development for academic advisors to provide personalized guidance, support, and resources to students, helping them make informed decisions and stay on track academically.